Metal-organic framework glass-coated composite solid electrolyte, method of preparation and use

CN122931008APending Publication Date: 2026-10-16NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611343861.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0005]针对现有固态电解质在空气中不稳定的问题,本发明提出了一种将晶态金属-有机框架与氧化物、硫化物固态电解质复合,在惰性气体氛围或真空条件下加热至晶态金属-有机框架的熔点以上,使其熔融流动并均匀包覆固态电解质颗粒,随后冷却固化,形成连续、致密且全包覆的金属-有机框架玻璃包覆层,从而构建核壳结构复合固态电解质

Benefits of technology

1)本发明公开的金属-有机框架玻璃包覆的复合固态电解质,利用玻璃的流动性,在固态电解质颗粒表面形成连续、均匀的保护层,有效阻隔空气中的水分、氧气和CO2,显著提高氧化物、硫化物等空气敏感型固态电解质的空气稳定性;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122931008A_ABST
    Figure CN122931008A_ABST
Patent Text Reader

Abstract

The application discloses a metal-organic framework glass coated composite solid electrolyte, a preparation method and application, the composite solid electrolyte is a core-shell coated composite solid electrolyte, the inner core is an inorganic solid electrolyte, and the shell is a metal-organic framework glass layer;The metal-organic framework glass layer is coated on the outer surface of the inorganic solid electrolyte;The metal-organic framework glass layer is a continuous full-coated layer formed by crystalline metal-organic framework material after melting and cooling solidification.The disclosed metal-organic framework glass coated composite solid electrolyte is used, the flowability of glass is utilized, a continuous and uniform protective layer is formed on the surface of solid electrolyte particles, water, oxygen and CO2 in air are effectively blocked, and the air stability of air-sensitive solid electrolyte such as oxide and sulfide is significantly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a metal-organic framework glass-coated composite solid electrolyte, its preparation method, and its application, belonging to the field of solid-state battery technology. Background Technology

[0002] Solid-state electrolytes are the core component of solid-state batteries. Among them, oxide solid-state electrolytes (such as LLZO and LATP), sulfide solid-state electrolytes (such as LGPS and Li6PS5Cl), and halide solid-state electrolytes (such as Li3YCl6 and Li3InCl6) have attracted widespread attention due to their high ionic conductivity and good mechanical properties. However, all three types of solid-state electrolytes exhibit varying degrees of instability in air. Specifically, oxide solid-state electrolytes are prone to structural damage due to surface reactions with moisture in the air and to the formation of insulating phases such as lithium carbonate with CO2, leading to increased interfacial impedance. Sulfide solid-state electrolytes are extremely sensitive to moisture, hydrolyzing to produce toxic hydrogen sulfide gas, while their ionic conductivity drops sharply. Halide solid-state electrolytes are prone to deliquescence and phase transitions in humid air, losing their ionic conductivity. This air instability severely hinders the large-scale production, storage, and transportation of solid-state electrolytes, as well as the subsequent manufacturing process of solid-state batteries, greatly increasing production difficulty and cost, and seriously impeding the industrialization of solid-state electrolytes.

[0003] To address these issues, researchers have primarily employed methods such as inorganic oxide coating deposition and polymer coating. However, inorganic coatings are prone to porosity and incomplete coverage, and exhibit poor interfacial bonding between the coating layer and the core electrolyte. Polymer coatings, on the other hand, lack sufficient heat resistance and barrier properties, making it difficult to achieve long-term air protection and easily increasing electrolyte interfacial impedance, thus affecting ion transport efficiency. Metal-organic frameworks (MOFs) are a class of porous crystalline materials composed of metal nodes and organic ligands. In recent years, it has been discovered that some MOFs melt into a fluid liquid melt when heated above their melting point, and can be transformed into amorphous MOF glasses upon rapid cooling. MOF glasses retain some of the porous structure and chemical characteristics of crystalline materials, exhibiting excellent chemical stability, along with advantages such as the absence of grain boundaries, fluidity and film-forming properties, strong bonding with solid electrolytes, and outstanding ion transport capabilities.

[0004] Based on the above advantages, this invention proposes to combine a crystalline metal-organic framework with an oxide or sulfide solid electrolyte, and heat it to above the melting point of the crystalline metal-organic framework under an inert gas atmosphere or vacuum conditions, so that it melts and flows and uniformly coats the solid electrolyte particles, and then cools and solidifies to form a continuous, dense and fully covered metal-organic framework glass coating layer, thereby constructing a core-shell structured composite solid electrolyte. Summary of the Invention

[0005] To address the instability of existing solid-state electrolytes in air, this invention proposes a method that combines a crystalline metal-organic framework (MOF) with an oxide or sulfide solid-state electrolyte. The MOF is heated above its melting point under an inert gas atmosphere or vacuum, causing it to melt and flow, uniformly coating the solid-state electrolyte particles. This is followed by cooling and solidification, forming a continuous, dense, and fully encapsulated MOF glass coating layer, thus constructing a core-shell composite solid-state electrolyte. This MOF glass coating layer effectively blocks moisture, oxygen, and CO2 from the air, significantly improving the air stability of the solid-state electrolyte. Simultaneously, utilizing the ion conductivity of MOF glass and its excellent interfacial wetting properties for electrolyte particles, the composite electrolyte maintains high ionic conductivity and electrochemical performance while achieving good environmental stability. This solves the key problem of poor air stability in existing inorganic solid-state electrolytes, facilitating its production, storage, transportation, and solid-state battery manufacturing.

[0006] According to a first aspect of the present invention, a metal-organic framework glass-coated composite solid electrolyte is provided, wherein the composite solid electrolyte is a core-shell coated composite solid electrolyte, the core being an inorganic solid electrolyte and the shell being a metal-organic framework glass layer; The metal-organic framework glass layer covers the outer surface of the inorganic solid electrolyte; The metal-organic framework glass layer is a continuous, fully encapsulated layer formed by melting and then cooling and solidifying crystalline metal-organic framework material.

[0007] Optionally, the crystalline metal-organic framework material includes at least one of the following: phosphate-imidazolium series, zeolite-imidazolium salt series, titanyl-hydroquinone series, thiocyanate, bis(fluorosulfonylimide)-nitrile framework series, metal-bis(acetamide) framework, carboxylic acid metal-organic framework, and pyridine-carboxylic acid metal-organic framework.

[0008] Optionally, the phosphate-imidazolium series is selected from at least one of [Zn(HPO4)(H2PO4)](H2Im)2, [Zn3(H2PO4)6(H2O)3](HbIm), [Zn3(H2PO4)6(H2O)3]H(2-MebIm), and [Zn3(H2PO4)6(H2O)3](BTA).

[0009] Optionally, the zeolite imidazole salt series is selected from at least one of ZIF-4, ZIF-7, ZIF-8, ZIF-62, and ZIF-76.

[0010] Optionally, the titanium oxide cluster-hydroquinone series is selected from Ti 16 O 16 (OEt) 32 Ti 12 O16 (O-iPr) 16 At least one of them.

[0011] Optionally, the thiocyanate is selected from at least one of Cu2(SCN)3 (C4bpy) and [Co(μ-NCS)2(C5H5N3O)2]·C5H5N3O.

[0012] Optionally, the bis(fluorosulfonyl)imide-nitrile framework series is Li[N(SO2F)2](NCCH2CH2CN)2.

[0013] Optionally, the metal-bis(acetamide) framework is selected from at least one of Co(hmba)3[Co(NCS)4], Co(bba)3[CoCl4], and Co(hmba)3[CoBr4].

[0014] Optionally, the carboxylic acid metal-organic framework is selected from at least one of UiO-67, UiO-68, DUT-5, and [Mg4(adipate)4(DMA)(H2O)].

[0015] Optionally, the pyridine-carboxylic acid metal-organic framework is [Mn3(peb)6]·2DMF.

[0016] Optionally, the thickness of the metal-organic framework glass layer is 2 nm to 20 nm, and the particle size of the inorganic solid electrolyte is 100 nm to 10 μm.

[0017] Optionally, the thickness of the metal-organic framework glass layer is independently selected from any value of 2 nm, 5 nm, 10 nm, 15 nm, 20 nm, or a range between any two of the above.

[0018] Optionally, the particle size of the inorganic solid electrolyte is independently selected from any value among 100 nm, 500 nm, 1 μm, 5 μm, 10 μm, or a range between any two of the above.

[0019] Optionally, the inorganic solid electrolyte includes at least one of oxide solid electrolyte, sulfide solid electrolyte, and halide solid electrolyte.

[0020] Optionally, the oxide solid electrolyte includes at least one of garnet type, perovskite type, and NASICON type.

[0021] Optionally, the garnet type is selected from at least one of LLZO and LLZTO.

[0022] Optionally, the perovskite type is LLTO.

[0023] Optionally, the NASICON type is selected from at least one of LZP, LTP, LGP, LATP, and LAGP.

[0024] Optionally, the sulfide solid electrolyte includes LPS system, LGPS type, silver-germanium sulfide type (Li6PS5X (X=Cl, Br, I)), glass type, glass-ceramic type sulfide or amorphous / glassy oxygen-containing sulfide solid electrolyte.

[0025] Optionally, the LPS system is selected from Li3PS4 and Li7P3S. 11 At least one of them.

[0026] Optionally, the halide solid electrolyte includes at least one of Li2MnCl4, Li3InCl6, and Li3YCl6.

[0027] According to a second aspect of the present invention, a method for preparing the above-described composite solid electrolyte is provided, the method comprising the following steps: A crystalline metal-organic framework material and an inorganic solid electrolyte are mixed evenly at a mass ratio of 0.5:99.5 to 50:50 to obtain a mixture. The mixture is heated to above the melting point of the crystalline metal-organic framework material under an inactive atmosphere or vacuum. The mixture is held at this temperature to allow the crystalline metal-organic framework material to completely melt and flow to coat the inorganic solid electrolyte particles. The mixture is then cooled to room temperature and solidified to obtain a composite solid electrolyte coated with a metal-organic framework glass.

[0028] Optionally, the heating temperature is 80~500 ℃, and the holding time is 1~180 min.

[0029] Optionally, the heating temperature is independently selected from any value of 80 ℃, 100 ℃, 150 ℃, 200 ℃, 250 ℃, 300 ℃, 350 ℃, 400 ℃, 450 ℃, 500 ℃ or a range between any two of the above.

[0030] Optionally, the heat preservation time is independently selected from any value of 1 min, 5 min, 10 min, 30 min, 50 min, 100 min, 120 min, 150 min, 180 min, or a range between any two of the above.

[0031] Optionally, the inactive atmosphere is selected from at least one of nitrogen, argon, and helium.

[0032] Optionally, the vacuum level of the vacuum condition is less than 10 Pa.

[0033] Optionally, the cooling rate is 0.5~50 °C / min.

[0034] According to a third aspect of the present invention, an application of the composite solid electrolyte described above or the composite solid electrolyte prepared by the preparation method described above in a solid-state battery is provided, wherein the composite solid electrolyte powder is coated or pressed by applying pressure to form a corresponding composite solid electrolyte membrane or composite solid electrolyte sheet, which is then assembled into a solid-state battery.

[0035] As an optional implementation, the present invention is achieved through the following technical solution: A method for preparing a metal-organic framework glass-coated composite solid electrolyte includes the following steps: (1) Mix the crystalline metal-organic framework material and the solid electrolyte at a mass ratio of 2:98 to 50:50. The mixing method can be ball milling, grinding or mechanical stirring, ball milling is preferred to promote uniform dispersion. (2) The mixture obtained in step (1) is heated to above the melting point of the crystalline metal-organic framework under an inert atmosphere (such as nitrogen, argon, helium) or vacuum conditions (vacuum degree below 10 Pa). The heating temperature is generally 80~500 ℃, and the temperature is held for 1~180 min, so that the crystalline metal-organic framework is completely melted and coated with solid electrolyte particles by means of its fluidity. (3) Cool to room temperature to solidify the molten metal-organic framework and obtain a solid electrolyte coated with a metal-organic framework glass. The cooling method can be quenching, natural cooling or programmed cooling, with a cooling rate of 0.5 to 50 °C / min.

[0036] Preferably, the solid electrolyte coated with metal-organic framework glass is prepared into a solid electrolyte membrane or a solid electrolyte sheet coated with metal-organic framework glass by applying pressure or coating.

[0037] Preferably, the obtained metal-organic framework glass-coated solid electrolyte membrane (sheet) is assembled into a button cell, pouch cell, cylindrical cell, or prismatic cell according to the structural layout of negative electrode, solid electrolyte, and positive electrode.

[0038] Preferably, the solid electrolyte is a solid electrolyte coated with a metal-organic framework glass.

[0039] Preferably, the cations that can be conducted by button, pouch, cylindrical, or prismatic batteries include any one of Li ions, Na ions, Mg ions, Ca ions, Al ions, K ions, Zn ions, and protons.

[0040] Preferably, the conductive cation is Li ion, which is a solid-state lithium battery, and the solid-state lithium battery is a solid-state battery in which Li ions are the charge carriers; When the cation is Na ion, it can be used as a solid sodium battery; When the cation is Mg ion, it can be a solid magnesium battery; When the cation is Ca ion, it can be used as a solid-state calcium battery; When the cation is K ion, it can be used as a solid potassium battery; When the cation is Zn ion, it can be used as a solid-state zinc battery; When the cation is Al ion, it can be used as a solid aluminum battery; When the cation is a proton, it can be used in a solid-state fuel cell.

[0041] The beneficial effects that this invention can produce include: 1) The metal-organic framework glass-coated composite solid electrolyte disclosed in this invention utilizes the fluidity of glass to form a continuous and uniform protective layer on the surface of solid electrolyte particles, effectively blocking moisture, oxygen and CO2 in the air, and significantly improving the air stability of air-sensitive solid electrolytes such as oxides and sulfides. 2) The metal-organic framework glass-coated composite solid electrolyte disclosed in this invention has an amorphous structure and excellent ion conductivity, and has good chemical compatibility and interfacial wettability with various solid electrolytes. This allows the core-shell structure composite solid electrolyte to achieve air stability while maintaining high ionic conductivity and electrochemical performance. It also balances air stability and ion transport performance, effectively avoiding the problem of sharp increase in interfacial impedance often introduced by traditional inert inorganic coatings or polymer coatings. 3) The preparation method of the metal-organic framework glass-coated composite solid electrolyte disclosed in this invention is simple and the conditions are mild (the maximum processing temperature does not exceed 500 ℃, which is lower than the decomposition temperature of most solid electrolytes), applicable to different types of solid electrolytes, and easy to scale up for production. At the same time, the metal-organic framework glass coating layer forms a tight and strong bond with the solid electrolyte core, which can withstand the mechanical stress during subsequent cycling. 4) The metal-organic framework glass-coated composite solid electrolyte disclosed in this invention solves the air sensitivity problem of solid electrolytes at the material level, reduces the stringent requirements for anhydrous and oxygen-free environments during production, storage and transportation, and is conducive to the commercial application of solid electrolytes. Attached Figure Description

[0042] Figure 1 This is a TEM image (scale bar is 10 nm) of MOF glass coated with LLZO prepared in Example 1 of the present invention. Figure 2This is a comparison of the cycling performance of MOF glass coated with LLZO and uncoated LLZO assembled LiFePO4||Li at a current density of 1 C, as shown in Example 1 of this invention. Detailed Implementation

[0043] The present invention will now be described in detail with reference to the embodiments, but the present invention is not limited to these embodiments.

[0044] Unless otherwise specified, the raw materials used in the embodiments of this invention were all purchased through commercial channels.

[0045] Example 1: LLZO (Li7La3Zr2O) coated with ZIF-62 metal-organic frame glass 12 Particles: S1: The oxide solid electrolyte is Li7La3Zr2O 12 (LLZO, garnet type, grain size D50=2 μm); S2: Crystalline metal-organic framework ZIF-62 and LLZO were mixed at a mass ratio of 5:95 and thoroughly mixed in a container. The mixture was transferred to an alumina crucible and placed in a tube furnace. Under an argon atmosphere, the temperature was increased to 460 °C at 2 °C / min and held for 60 minutes. It was then allowed to cool naturally to room temperature to obtain ZIF-62 glass-coated LLZO composite powder, wherein the thickness of the metal-organic framework glass layer was approximately 3 nm. Figure 1 As shown, MOF glass is uniformly coated on the LLZO surface, with a coating thickness of approximately 3 nm. The interface between the coating and the LLZO substrate is clear and tightly bonded, with no obvious pores or cracks observed. S3: LLZO particles coated with ZIF-62 metal-organic framework glass were cold-pressed into sheets or coated onto flexible substrates such as diaphragms, and their ionic conductivity was tested using AC impedance spectroscopy. The results showed that the ionic conductivity was 0.7 mS / cm (room temperature) after 30 days of exposure to air with a relative humidity of 30%.

[0046] Comparative Example 1:

[0047] After 30 days of exposure under the same conditions, the ionic conductivity of uncoated LLZO decreased to 0.37 mS / cm, which was only 53% of the initial value.

[0048] Electrochemical performance testing: The metal-organic framework glass-coated LLZO (ZIF-62 glass@LLZO) prepared in Example 1 was used as a solid electrolyte and assembled into an all-solid-state battery with a LiFePO4 cathode and a lithium metal anode. Cyclic testing was conducted at 25°C and 1 C current density. The results are as follows: Figure 2As shown, the initial discharge specific capacity was 130 mAh / g, and the capacity retention rate after 300 cycles was 94.6%. In contrast, when assembling batteries using uncoated LLZO, the internal resistance of the battery increased significantly due to the formation of a Li2CO3 insulating layer on the surface of LLZO after exposure to air, resulting in an initial capacity of only 83 mAh / g. Therefore, it is fully demonstrated that the ZIF-62 glass coating not only significantly improves the air stability of LLZO by physically isolating it from moisture, oxygen, and CO2 and inhibiting the formation of Li2CO3 on the surface, but also achieves a balance between air stability and high ionic conductivity due to the inherent ion conductivity of ZIF-62 glass and its excellent interfacial wetting properties with LLZO particles.

[0049] Example 2: LLZO (Li7La3Zr2O) coated with ZIF-4 metal-organic frame glass 12 Particles: S1: The oxide solid electrolyte is Li7La3Zr2O 12 (LLZO, garnet type, grain size D50=2 μm); S2: Crystalline metal-organic framework ZIF-4 and LLZO were mixed at a mass ratio of 30:70 and thoroughly mixed in a container. The mixture was then transferred to an alumina crucible and placed in a tube furnace. Under an argon atmosphere, the temperature was increased to 470 °C at 2 °C / min and held for 60 minutes. The mixture was then allowed to cool naturally to room temperature to obtain ZIF-4 glass-coated LLZO composite powder, wherein the thickness of the metal-organic framework glass layer was approximately 15 nm. S3: LLZO particles coated with ZIF-4 metal-organic framework glass were exposed to air at 30% relative humidity for 60 days, followed by cold pressing into sheets. The ionic conductivity was tested using AC impedance spectroscopy. The results showed that the ionic conductivity after exposure was 0.57 mS / cm (room temperature).

[0050] Example 3: LLZTO (Li) coated with ZIF-4 metal-organic frame glass 6.4 La3Zr 1.4 Ta 0.6 O 12 Particles: S1: Li-based oxide solid electrolyte is selected. 6.4 La3Zr 1.4 Ta 0.6 O 12 (LLZTO, garnet type, grain size D50=1 μm); S2: Crystalline metal-organic framework ZIF-4 and LLZTO were mixed at a mass ratio of 50:50 and thoroughly mixed in a container. The mixture was transferred to an alumina crucible and placed in a tube furnace. Under an argon atmosphere, the temperature was increased to 470℃ at 5℃ / min and held for 120 minutes. The mixture was then rapidly cooled to room temperature to obtain ZIF-4 glass-coated LLZTO composite powder, wherein the thickness of the metal-organic framework glass layer was approximately 20 nm. S3: LLZTO particles coated with ZIF-4 metal-organic framework glass were exposed to air at 30% relative humidity for 30 days, followed by cold pressing into sheets. The ionic conductivity was tested using AC impedance spectroscopy. The results showed that the ionic conductivity after exposure was 0.46 mS / cm (room temperature).

[0051] Example 4: Li6PS5Cl particles coated with ZIF-62 metal-organic framework glass: S1: The sulfide solid electrolyte is Li6PS5Cl (particle size D50=5 μm). S2: Crystalline metal-organic framework ZIF-62 and Li6PS5Cl were mixed at a mass ratio of 2:98 and thoroughly mixed in a container. The mixture was transferred to an alumina crucible and placed in a tube furnace. Under an argon atmosphere, the temperature was increased to 440 °C at 3 °C / min and held for 30 minutes. The mixture was then allowed to cool naturally to room temperature to obtain ZIF-62 glass-coated Li6PS5Cl composite powder, wherein the thickness of the metal-organic framework glass layer was approximately 3 nm. S3: Li6PS5Cl particles coated with ZIF-62 metal-organic framework glass were exposed to air at 30% relative humidity for 5 days, followed by cold pressing into sheets. The ionic conductivity was tested using AC impedance spectroscopy. The results showed that the ionic conductivity was 0.21 mS / cm after 5 days of exposure.

[0052] Example 5: Li6PS5Cl particles coated with ZIF-62 metal-organic framework glass: S1: The sulfide solid electrolyte is Li6PS5Cl (particle size D50=5 μm). S2: Crystalline metal-organic framework ZIF-62 and Li6PS5Cl were mixed at a mass ratio of 2:98 and thoroughly mixed in a container. The mixture was then transferred to an alumina crucible and placed in a tube furnace. Under an argon atmosphere, the temperature was increased to 460 °C at 3 °C / min and held for 30 minutes. The mixture was then allowed to cool naturally to room temperature to obtain ZIF-62 glass-coated Li6PS5Cl composite powder, wherein the thickness of the metal-organic framework glass layer was approximately 3 nm. S3: Li6PS5Cl particles coated with metal-organic frame glass ZIF-62 were exposed to air with a relative humidity of 60% for 5 days, and then cold-pressed into sheets. The ionic conductivity was tested by AC impedance method and found to be 0.1 mS / cm.

[0053] Table 1 shows the relevant parameters for ionic conductivity testing in Examples 1-5 and Comparative Example 1:

[0054] It should be noted that while the coating provides protection, the absolute conductivity of the composite material is slightly lower than that of the original sulfide because the ionic conductivity of the metal-organic frame glass (MOF glass) is slightly lower than that of the high-performance sulfide electrolyte. However, its air stability is improved by orders of magnitude, resulting in better overall performance.

[0055] In summary, the metal-organic framework glass-coated composite solid electrolyte disclosed in this invention utilizes the fluidity of glass to form a continuous and uniform protective layer on the surface of solid electrolyte particles, effectively blocking moisture, oxygen, and CO2 in the air, and significantly improving the air stability of air-sensitive solid electrolytes such as oxides and sulfides.

[0056] The above description is merely a preferred embodiment of the present invention and does not limit the patent scope of the present invention. Any equivalent structural or procedural transformations made based on the content of the present invention specification, or direct or indirect applications in other related technical fields, are similarly included within the patent protection scope of the present invention.

[0057] It should be noted that, in this document, the terms “comprising,” “including,” or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.

[0058] The above description is merely a few embodiments of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any modifications or alterations made by those skilled in the art without departing from the scope of the technical solution of the present invention using the disclosed technical content are equivalent to equivalent implementation cases and fall within the scope of the technical solution.

Claims

1. A composite solid electrolyte coated with a metal-organic framework glass, characterized in that, The composite solid electrolyte is a core-shell coated composite solid electrolyte, with an inorganic solid electrolyte core and a metal-organic framework glass layer as the shell. The metal-organic framework glass layer covers the outer surface of the inorganic solid electrolyte; The metal-organic framework glass layer is a continuous, fully encapsulated layer formed by melting and then cooling and solidifying crystalline metal-organic framework material.

2. The composite solid electrolyte according to claim 1, characterized in that, The crystalline metal-organic framework materials include at least one of the following: phosphate-imidazolium series, zeolite-imidazolium salt series, titanyl group-hydroquinone series, thiocyanate, bis(fluorosulfonylimide)-nitrile framework series, metal-bis(acetamide) framework, carboxylic acid metal-organic framework, and pyridine-carboxylic acid metal-organic framework. The phosphate-imidazolium series is selected from at least one of [Zn(HPO4)(H2PO4)](H2Im)2, [Zn3(H2PO4)6(H2O)3](HbIm), [Zn3(H2PO4)6(H2O)3]H(2-MebIm), and [Zn3(H2PO4)6(H2O)3](BTA); The zeolite imidazole salt series is selected from at least one of ZIF-4, ZIF-7, ZIF-8, ZIF-62, and ZIF-76; The titanium oxide cluster-hydroquinone series is selected from Ti 16 O 16 (OEt) 32 Ti 12 O 16 (O-iPr) 16 At least one of them; The thiocyanate is selected from at least one of Cu2(SCN)3 (C4bpy) and [Co(μ-NCS)2(C5H5N3O)2]·C5H5N3O; The difluorosulfonylimide-nitrile framework series is Li[N(SO2F)2](NCCH2CH2CN)2; The metal-bis(acetamide) framework is selected from at least one of Co(hmba)3[Co(NCS)4], Co(bba)3[CoCl4], and Co(hmba)3[CoBr4]. The carboxylic acid metal-organic framework is selected from at least one of UiO-67, UiO-68, DUT-5, and [Mg4(adipate)4(DMA)(H2O)]. The pyridine-carboxylic acid metal-organic framework is [Mn3(peb)6]·2DMF.

3. The composite solid electrolyte according to claim 1, characterized in that, The thickness of the metal-organic framework glass layer is 2 nm to 20 nm, and the particle size of the inorganic solid electrolyte is 100 nm to 10 μm.

4. The composite solid electrolyte according to claim 1, characterized in that, The inorganic solid electrolyte includes at least one of oxide solid electrolyte, sulfide solid electrolyte, and halide solid electrolyte; The oxide solid electrolyte includes at least one of garnet type, perovskite type, and NASICON type; The garnet type is selected from at least one of LLZO and LLZTO; The perovskite type is LLTO; The NASICON type is selected from at least one of LZP, LTP, LGP, LATP, and LAGP; The sulfide solid electrolyte includes LPS system, LGPS type, silver-germanium sulfide type (Li6PS5X (X=Cl, Br, I)), glass type, glass-ceramic type sulfide or amorphous / glassy oxygen-containing sulfide solid electrolyte. The LPS system is selected from Li3PS4 and Li7P3S. 11 At least one of them; The halide solid electrolyte includes at least one of Li2MnCl4, Li3InCl6, and Li3YCl6.

5. The method for preparing the composite solid electrolyte according to any one of claims 1 to 4, characterized in that, The preparation method includes the following steps: A crystalline metal-organic framework material and an inorganic solid electrolyte are mixed evenly at a mass ratio of 0.5:99.5 to 50:50 to obtain a mixture. The mixture is heated to above the melting point of the crystalline metal-organic framework material under an inactive atmosphere or vacuum. The mixture is held at this temperature to allow the crystalline metal-organic framework material to completely melt and flow to coat the inorganic solid electrolyte particles. The mixture is then cooled to room temperature and solidified to obtain a composite solid electrolyte coated with a metal-organic framework glass.

6. The preparation method according to claim 5, characterized in that, The heating temperature is 80~500 ℃, and the holding time is 1~180 min.

7. The preparation method according to claim 5, characterized in that, The inactive atmosphere is selected from at least one of nitrogen, argon, and helium.

8. The preparation method according to claim 5, characterized in that, The vacuum level of the vacuum condition is less than 10 Pa.

9. The preparation method according to claim 5, characterized in that, The cooling rate is 0.5~50 ℃ / min.

10. The application of the composite solid electrolyte according to any one of claims 1 to 4 or the composite solid electrolyte prepared by the preparation method according to any one of claims 5 to 9 in a solid-state battery, characterized in that, Composite solid electrolyte powder is coated or pressed into sheets by applying pressure to prepare corresponding composite solid electrolyte membranes or sheets, which are then assembled into solid-state batteries.